Early Childhood Studies : An holistic introduction - Taylor, Jayne; Woods, Margaret (London : Arnold, 1998)
This text is aimed at students studying early childhood as a component of an academic course. Aspects of growth, social provision, psychology, nutrition, health and the law are explored in relation to child development.
Includes bibliographical references and index.
Keywords: Child development; Child care; Child Care